Prevalence of and Risk Factors for Total Hip and Knee Replacement in Retired National Football League Athletes. Issue 12 (October 2019) - Davies, Madeleine A.M.; Kerr, Zachary Y.; DeFreese, J.D.; Arden, Nigel K.; Marshall, Stephen W.; Guskiewicz, Kevin M.; Padua, Darin A.; Pietrosimone, Brian
Background: Osteoarthritis is a substantial cause of disability. Joint replacement prevalence relates to the burden of severe osteoarthritis, and identifying risk factors for end-stage disease may indicate intervention opportunities. American football has high youth and elite participation, and determining risk factors for severe osteoarthritis may support future morbidity prevention. Purpose: To (1) determine the prevalence of hip and knee replacement in retired National Football League (NFL) athletes, (2) examine risk factors for replacement, and (3) identify the association between knee injuries and knee replacement. Study Design: Case-control study; Level of evidence, 3. Methods: Retired NFL athletes who participated in a general health survey were included. This historical cohort included those playing between 1929 and 2001. The association between self-reported playing or injury history, and replacement after retirement, was assessed with prevalence ratios (PRs). Models were adjusted for potential confounders of age and weight. Results: Data for 2432 retired male NFL players (69.3% response rate) who had participated in football for a mean 15.2 years were included, in which 277 players reported replacement after retirement (11.4%). More participants reported knee replacement (7.7%) than hip replacement (4.6%). The majority of participants reported previous severe knee injury (53%), and the most prevalent was meniscal tear (32.2%). In multivariable models, age (10-year increase, PR, 2.23; 95% CI, 1.99-2.51), current weight (PR, 1.10; 95% CI, 1.06-1.14), and reporting 1 (PR, 1.78; 95% CI, 1.14-2.77), 2 (PR, 1.91; 95% CI, 1.16-3.15), or ≥3 knee injuries (PR, 3.44; 95% CI, 2.33-5.09) were associated with knee replacement. Age (10-year increase, PR, 1.86; 95% CI, 1.59-2.18), linemen (PR, 1.62; 95% CI, 1.03-2.55), and reporting 1 (PR, 1.72; 95% CI, 1.05-2.80), 2 (PR, 2.77 95% CI, 1.58-4.84), or ≥3 (PR, 2.44; 95% CI, 1.52-3.91) hip injuries were associated with hip replacement. Each reported knee injury type was cross-sectionally associated with replacement after retirement ( P < .05). Conclusion: Knee replacement was more prevalent than hip replacement. Risk factors differed between the hip and the knee, with age and severe joint injury associated with hip and knee replacement, weight with knee replacement, and playing position associated with hip replacement. Joint injury and weight management may be prevention opportunities to reduce morbidity and end-stage osteoarthritis in this population.